Pengaruh Model Pembelajaran Kooperatif Tipe TAI terhadap Pemahaman Konsep Matematis Peserta Didik Kelas VIII SMP Negeri 2 Kota Solok - TRIO KEPHI (Departemen Matematika, 2019)
One of the basic abilities of mathematics is concept understanding. In the process of learning mathematic at all levels of education requires understanding concepts to solve problems and develop other mathematical abilities. Based on the test results, understanding of the mathematical concept of students at SMP Negeri 2 Kota Solok is still low. One way to improve it is to use a Team Assisted Individualization (TAI) model. The purpose of this study is to compare the understanding of mathematical concept of students who learn to use the TAI model with those who learn to use conventional learning model and describe the development of students understanding of mathematical concept while using the TAI model. This type of research is quasi-experimental and descriptive research with Static Group Design research design. Based on the results obtained from the data analysis, it can be concluded that the understanding of mathematical concept of students who learn using the TAI model is better than students who learn with conventional learning models class VIII of SMP Negeri 2 Kota Solok and the development of mathematical understanding of students learning with the TAI model also increases . Keywords – Cooperative Learning Model, Mathematical Concept Understanding, Team Assisted Individualization Model